2012
DOI: 10.1097/ta.0b013e318270d3ee
|View full text |Cite
|
Sign up to set email alerts
|

Blast injury in children

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 16 publications
3
25
1
1
Order By: Relevance
“…[5] Edwards et al in their study of 4,983 blast injury among civilian patients in Afghanistan and Iraq; in this cohort, 25% were children younger than 15 years and also reported that injuries in children were more likely to occur in the head and neck and less likely in the bony pelvis (perineum) and extremities. [13] This is corroborated by the findings in other studies. [6,7] Blast injuries tend to affect multiple parts of the body.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[5] Edwards et al in their study of 4,983 blast injury among civilian patients in Afghanistan and Iraq; in this cohort, 25% were children younger than 15 years and also reported that injuries in children were more likely to occur in the head and neck and less likely in the bony pelvis (perineum) and extremities. [13] This is corroborated by the findings in other studies. [6,7] Blast injuries tend to affect multiple parts of the body.…”
Section: Discussionsupporting
confidence: 85%
“…Edwards et al in their study of 4983 children presenting with blast injuries reported a mortality rate of 8%. [13] However, Thompson et al reported mortality over double that of Edwards et al (18%). [14] This was attributed to operational tempo and increasing use of improvised explosive devices.…”
Section: Discussionmentioning
confidence: 92%
“…18 As such, there exists an ever-evolving definition of pediatric massive transfusion (Table 1). 3,16,17,[19][20][21]…”
Section: Definition Of Massive Transfusion In Childrenmentioning
confidence: 99%
“…Additional etiologies of life-threatening hemorrhage include operative complications, invasive tumors whose removal results in significant blood loss, liver surgery and gastrointestinal bleeding. [3][4][5][6] Despite these varied reasons for hemorrhage, traumatic injury remains the main driver for activation of a pediatric MTP. This subset of trauma victims is generally older, more hypothermic, with a higher injury severity score when compared with other pediatric trauma patients who may have been transfused but did not meet the criteria for pediatric massive transfusion (MT).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of paediatric wartime mortality data is difficult as many studies do not differentiate mechanism of injury. Edwards et al ’s41 study on 4913 children between 2002 and 2010 presenting with blast injuries remains the single largest data set. The reported mortality rate of 8% matches well with the mortality rates of 6%–9% quoted in paediatric trauma deaths from Iraq and Afghanistan, although these studies displayed all trauma mechanisms as opposed to specifying blast trauma 35 42–46.…”
Section: Resultsmentioning
confidence: 99%